#TITLE_ALTERNATIVE# - NURFAHRUDIN (NIM:10209047); Pembimbing : Dr. Nurhasan, S.Si.,M.Si., IWAN
Time Domain Electromagnetic Method (TDEM) is an electromagnetic method in geophysics measuring transient of magnetic field depending on time because of the existence of secondary electrical current induction. In TDEM, similar with another electromagnetic method, is able determine a rock structure in the subsurface by resistivity or conductivity parameter. The data are transient of the secondary magnetic field received by the receiver unit and scripted into a curve of voltage and time. Processing and modeling the data is the next step in this experiment. Before used to real field data, this experiment was to analyze resistivity structure by 1-dimensional forward modeling of TDEM. The 1-dimension modeling in this method is applied for the data from area of X. Based on processing the data, it concludes that the subsurface structure is arranged by sandstone and clay.